1985
DOI: 10.1177/030098588502200110
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Canine Parvovirus Enteritis: The Importance of Viremia

Abstract: Abstract. The clinical signs, hematologic changes, serum and fecal virus titers, specific antibody production and the occurrence of histologic lesions were studied in 22 nine-week-old seronegative beagle dogs inoculated by the oral and intravenous route with canine parvovirus. Approximately 30% of the dogs had clinical signs of pyrexia, depression, vomiting, and diarrhea irrespective of the route of inoculation. Events in the dogs inoculated intravenously preceded those in dogs inoculated orally by approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 16 publications
3
59
0
3
Order By: Relevance
“…However, there is obviously not a simple relationship between feline TfR inactivation and cat infection, as the soluble feline TfR also inhibited FPV binding and infection of cells. Explanations would be that FPV circulates in a cell-associated form in cats, while CPV-2 circulates as a free viremia (as it does in dogs) and therefore is readily inactivated (11,43,62). However, the comparative pathogenesis of the different viruses is not sufficiently well understood to allow us to determine the mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is obviously not a simple relationship between feline TfR inactivation and cat infection, as the soluble feline TfR also inhibited FPV binding and infection of cells. Explanations would be that FPV circulates in a cell-associated form in cats, while CPV-2 circulates as a free viremia (as it does in dogs) and therefore is readily inactivated (11,43,62). However, the comparative pathogenesis of the different viruses is not sufficiently well understood to allow us to determine the mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%
“…In the present experiments, rFeIFN-ω was administered on day 4 after virus inoculation when CPV-2 replication has already spread resulting in cytological effects on germinal epithelium of the intestinal crypts and in the appearance of enteritis [15,17,18]. The ameliorating effect of treatment of CPV-2-infected dogs with rFeIFN-ω, therefore, appears to be due to not only its antiviral activity, but to other functions of IFNs, such as enhancement of immune systems in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Meunier et al [18] reported that 10 5 TCID 50 of CPV caused clinical signs in about 30% of infected beagle dogs. In the present experiments, inoculation of 10 7 TCID 50 of CPV-2 (cc 238 strain) induce clinical symptoms in all exposed SPF animals, although the severity of symptoms were milder than natural disease.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of the intestinal villi were typical of CCV infection S 1,8,9 however, basophilic intranuclear inclusion bodies in crypt epithelial cells, as well as necrosis and depletion of lymphoid tissue, are characteristic findings in CPV but not CCV infections. 4,11 Those findings notwithstanding, cells still infected by CPV-2b would not be expected to persist 3 weeks after the initial infection, 11 and CPV-2b was not demonstrated in the pups' feces by HA or the IFAT. Furthermore, experimental studies on CPV-2b pathogenesis in pups failed to reveal virus, or viral DNA in tissues Ͼ6 days after oronasal infection by virus isolation or in situ DNA hybridization methods (D. Peters, unpublished data).…”
mentioning
confidence: 98%